Trypanosoma cruzi infection results in an increase in intracellular cholesterol - Johndrow, Christopher (2014)
Chagasic cardiomyopathy caused by Trypanosoma cruzi is a major health concern in Latin America and among immigrant populations in non-endemic areas. T. cruzi has a high affinity for host lipoproteins and uses the low density lipoprotein receptor (LDLr) for invasion. Herein, we report that T. cruzi infection is associated with an accumulation of LDL and cholesterol in tissues in both acute and chronic murine Chagas disease. Similar findings were observed in tissue samples from a human case of Chagasic cardiomyopathy. T. cruzi infection of cultured cells displayed increased invasion with increasing cholesterol levels in the medium. Studies of infected host cells demonstrated alterations in their cholesterol regulation. T. cruzi invasion/infection via LDLr appears to be involved in changes in intracellular cholesterol homeostasis. The observed changes in intracellular lipids and associated oxidative stress due to these elevated lipids may contribute to the development of Chagasic cardiomyopathy.